2017
DOI: 10.1159/000455257
|View full text |Cite
|
Sign up to set email alerts
|

Solifenacin in the Elderly: Results of an Observational Study Measuring Efficacy, Tolerability and Cognitive Effects

Abstract: Introduction: The study aimed to evaluate the efficacy and safety of solifenacin in older patients with overactive bladder (OAB). Materials and Methods: Observational data on patients aged ≥70 years and the prescribed flexible dose of solifenacin for OAB were collected at 294 offices of German general practitioners. Baseline and week 12 data included type and severity of OAB symptoms, adverse events, quality of life, and change in cognitive function per Mini Mental State Examination (MMSE). Results: Mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
12
0
3
Order By: Relevance
“…Although β 3 ‐adrenoceptors were originally believed to be resistant to agonist‐induced desensitization, it is now clear that these receptors at least in some tissues and cell types can undergo desensitization; whether this also applies to the human bladder in vivo remains unclear. Similar to muscarinic antagonists, the efficacy of mirabegron relative to placebo was only moderate in controlled studies, but considerably larger in a non‐interventional study …”
Section: Defining the Medical Need: Efficacymentioning
confidence: 95%
See 1 more Smart Citation
“…Although β 3 ‐adrenoceptors were originally believed to be resistant to agonist‐induced desensitization, it is now clear that these receptors at least in some tissues and cell types can undergo desensitization; whether this also applies to the human bladder in vivo remains unclear. Similar to muscarinic antagonists, the efficacy of mirabegron relative to placebo was only moderate in controlled studies, but considerably larger in a non‐interventional study …”
Section: Defining the Medical Need: Efficacymentioning
confidence: 95%
“…Similar to muscarinic antagonists, the efficacy of mirabegron relative to placebo was only moderate in controlled studies, 16 but considerably larger in a non-interventional study. 32 Based on their different routes of administration and approved indications, randomized comparative trials between onabotulinumtoxinA and oral medications have not been reported. Randomized studies have shown effects in OAB patients that had experienced an insufficient therapeutic response to muscarinic antagonists, but the difference relative to placebo was moderate in most studies.…”
Section: Defining the Medical Need: Efficacymentioning
confidence: 99%
“…In addition, two recent studies showed that antimuscarinics had no significant effect on cognitive function in the elderly. The first study showed that solifenacin was well tolerated, while OAB symptoms declined at week 12 with no relevant effect of solifenacin on cognitive function observed in this elderly population [50]. The second study showed that flexible dose fesoterodine significantly improved UUI episodes and other outcomes versus placebo and was generally well tolerated in a community of significantly older, medically complex elderly population with UUI [51].…”
Section: Pharmacotherapy In the Elderlymentioning
confidence: 95%
“…Хворі літнього віку соліфенацин переносили добре, водночас спостерігалося зменшення всіх симптомів гіперактивності сечовипускання, включаючи зменшення терміновості сечовипускання і не спостерігалося відповідного впливу соліфенацину на когнітивні функції. Несприятливі події і припинення лікування були низькими -5,8% і 0,5% відповідно [37]. Чоловіки з тяжкими симптомами ГСМ продемонстрували об'єктивне і суб'єктивне поліпшення симптомів, зниження занепокоєння з приводу симптомів при застосуванні соліфенацину [38].…”
Section: в п о м о щ ь п р а к т и ч е с к о м у в р а ч уunclassified
“…Беззаперечно важливим є приєднання вторинних ускладнень у формі інфекційно-запального процесу у сечостатевих шляхах (цистит, простатит, уретрит), що характеризуються низькою антибактеріальною активністю слизової оболонки. Саме тому наявність мимовільних скорочень детрузора (імперативні поклики до мікції), формування хронічної ретенції сечі (залишкова сеча) та феномен зворотного -клінічні (оцінювання чутливості в сакральних сегментах, анального і бульбокавернозного рефлексів, що замикаються на S5 і L5-S5 рівнях відповідно; проведення клінічного оцінювання розладів сечовипускання за допомогою шкал і таблиць -щоденник сечовипускань, шкали IPSS, QOL та уродинамічних досліджень) [24,25];…”
unclassified